2019
DOI: 10.3389/fped.2019.00198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prematurity on the Cutaneous Microcirculatory Network in the First Weeks of Life

Abstract: Background: Preterm infants are at increased risk for hypertension in adolescence. Microcirculatory dysfunction has been identified as an underlying cause for cardiovascular disease. Our goal was to document the development of the cutaneous microcirculation in preterm infants during the first weeks of life and to compare it to the situation in term infants at birth. Methods: In 20 preterm infants, microcirculatory parameters were obtained prospectively by Sidestream Dark Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…More than 20 years ago, it was already suggested that early impairment of vascular structure in fetal life might not be reversible and thus contribute to long term vascular sequelae 43 . In line with this notion, we have been able to show that preterm neonates have a characteristic vascular phenotype with increased vessel density that persists into adolescence 6 , 11 . In support of our previous results, the present study also showed higher vessel densities in preterm neonates compared to term infants.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…More than 20 years ago, it was already suggested that early impairment of vascular structure in fetal life might not be reversible and thus contribute to long term vascular sequelae 43 . In line with this notion, we have been able to show that preterm neonates have a characteristic vascular phenotype with increased vessel density that persists into adolescence 6 , 11 . In support of our previous results, the present study also showed higher vessel densities in preterm neonates compared to term infants.…”
Section: Discussionsupporting
confidence: 75%
“…Alterations in microvascular architecture and function associated with prematurity may play a role in the development of hypertension 9,10 . In a previous study, we were able to demonstrate that premature neonates exhibit a distinct microvascular phenotype compared to mature neonates that persists throughout the first month of life and even into adolescence 6,11 . Furthermore, several studies reported a disturbed endothelial function-considered a key factor in the development of vascular disease-in low birth weight neonates [12][13][14][15] .…”
mentioning
confidence: 87%
“…In an analysis of premature infants (gestational age, 24-34 weeks), a distinct premature microvascular phenotype was characterized through non-invasive in vivo photothermal imaging technology. 8 Compared with healthy age-matched full-term neonates, premature infants have an increased density of proportionately smaller-diameter vessels, resulting in an overall lower cutaneous surface area covered by vessels. Interestingly, this premature vascular phenotype persists, as the infants reach term age, and is not yet organized until 14-17 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Intravital recordings of the sublingual microcirculation were performed using Sidestream Dark Field (SDF) imaging technology as previously described [16,17]. Images were obtained with the Microscan videomicroscope (5x-magnification; Microvision Medical, Amsterdam, Netherlands) by two researchers not involved in patient care.…”
Section: Recordings and Analysis Of The Microcirculationmentioning
confidence: 99%